Genomics and proteomics engineering in medicine and biology - Akay, Metin (John Wiley, 2007)
Current applications and recent advances in genomics and proteomics Genomics and Proteomics Engineering in Medicine and Biology presents a well-rounded, interdisciplinary discussion of a topic that is at the cutting edge of both molecular biology and bioengineering. Compiling contributions by established experts, this book highlights up-to-date applications of biomedical informatics, as well as advancements in genomics-proteomics areas. Structures and algorithms are used to analyze genomic data and develop computational solutions for pathological understanding. Topics discussed include:* Qualitative knowledge models* Interpreting micro-array data* Gene regulation bioinformatics* Methods to analyze micro-array* Cancer behavior and radiation therapy* Error-control codes and the genome* Complex life science multi-database queries* Computational protein analysis* Tumor and tumor suppressor proteins interactions